ARISTOPHANES VS TYPHON: CO(S)MIC RIVALRY, VOICE AND TEMPORALITY IN KNIGHTS. (4th June 2014) - Telò, Mario
<x content-type="archive" xml:space="preserve">Abstract</x> Recent studies have analysed the essential role of interpoetic rivalry in Aristophanes' comic imagination. Zachary Biles has shown that 'festival agonistics provide an underlying logic for the overall thematic design of individual plays' and that 'the plays can be treated as creative responses to the competitions.' Aristophanes' dramatisation of comic competition has been viewed as a reflection of the struggles of political factions in late-fifth-century Athens or as an expression of a 'rhetoric of self-promotion' that builds the comic plot through the mutual borrowing of comic material (jokes, running gags). This paper suggests that Knights presents interpoetic rivalry as a conflict of embodied aesthetic modes. In this play, Aristophanes' tendentious definition of his comic self against his predecessor Cratinus results in opposed ways of conceptualising the sonic quality of dramatic performance and its material effects on the audience. The nexus of voice and temporality, which, as I argue, shapes the play's agonistic plot, equates the intergenerational duelling of Aristophanes' and Cratinus' political counterparts (the Sausage Seller and the older Paphlagon, respectively) to a contrast of somatic experiences grounded in sound.